Work Environment Factors and Employee Productivity - Bello, Mohammed Lawan; AbdulKareem, Abdulrazaq Kayode; Adeyemi, Farida Omotoyosi; Isiaka, Sulu Babaita; Amosa, Rafiu Jimoh (Journal of Techno-Social, 2026)
This study investigates the relationship between work environment factors and employee productivity among bursary staff at the University of Ilorin, Nigeria. Using a quantitative approach, the research examines how workplace safety and workload influence employee performance through the theoretical lenses of Herzberg's Two-Factor Theory and Affective Events Theory. Data was collected from 87 bursary staff members using a structured questionnaire, achieving a 100% response rate. Analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed significant relationships between both workplace safety (β = 0.323, p < 0.001) and workload (β = 0.544, p < 0.001) with employee productivity. The model explained 57.5% of the variance in employee productivity. The findings demonstrate that proper workload management and workplace safety measures significantly enhance employee productivity in university administrative settings. These results provide valuable insights for university administrators and policymakers in developing strategies to improve work environments and boost staff performance in Nigerian higher education institutions.